PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN JASA RANAHCREATIVE DI JABODETABEK - Mitta Amelia Agustine (2021)
In the Ranahcreative service, there are several consumers who have canceled the use of the service. The research purpose of this study is to determine: the effect of brand image on consumer purchasing decisions of Ranahcreative in Jabodetabek, either partially or simultaneously. The research methodology used is quantitative with a population of 134 consumers of Ranahcreative. The population of this research was 100 respondents and the sample was selected by using simple random sampling as a sampling technique. The data were collected by means of a questionnaire and using a PLS (Partial Least Square) calculation tool. The results of this research showed that: (1) purchasing decisions can be influenced by brand image. (2) purchasing decisions can also be influenced by price. (3) the purchasing decision is also influenced simultaneously by brand image and price variables.